Mobile-assisted reading development: a review from the Activity Theory perspective. Issue 8 (1st November 2020) - Lin, Chih-Chung; Lin, Vivien; Liu, Gi-Zen; Kou, Xiaojing; Kulikova, Alena; Lin, Wenling
Abstract: Little review research has been conducted to describe the interaction and inter-relationships among components of reading development facilitated through mobile assisted language learning (MALL). The language learners, mediation via mobile devices, learning context, learning material and tasks, and learning outcomes need to be carefully examined in mobile-assisted reading. Hence, 28 empirical studies on mobile-assisted reading research published between 2008 and 2018 were selected and evaluated by the Activity Theory (AT) model. The investigators explored the research design of the studies and examined how reading development through mobile-assisted reading could be interpreted from seven constituents of AT – tool, subject, object, rules, community, division of labor, and outcome. In addition, facilitating processes conducive to reading development were analyzed. Based on the desired outcomes achieved by the facilitating processes, design-, strategy-, and learner-related guidelines for reading development in MALL were proposed. The ultimate goal of MALL for fostering self-regulated learning is also discussed. The review provides instructors and researchers with detailed sociocultural accounts and recommendations for the design and implementation of reading in MALL.